Executive Functioning in 60+ Autistic Males: The Discrepancy Between Experienced Challenges and Cognitive Performance - Geurts, Hilde M. (J Autism Dev Disord, 2020)
As executive functioning (EF) is especially sensitive to age-related cognitive decline, EF was evaluated by using a multi-method assessment. Fifty males (60–85 years) with a late adulthood autism spectrum condition (ASC) diagnosis and 51 non-ASC males (60–83 years) were compared on cognitive tests across EF domains (cognitive flexibility, planning, processing speed, and working memory) and a self- and proxy report of the Behavior Rating Inventory of Executive Function-Adult Version. While no objective performance differences emerged, autistic males and their proxies did report more EF challenges than non-ASC males on the subjective measure. In order to know how to support the older autistic men who received their ASC diagnosis in late adulthood with their daily life EF challenges, it is important to understand what underlies these subjective EF problems.